"Economic support? They don't really need it". Prejudice towards Latin American immigrants in Argentina. (March 2022) - Etchezahar, Edgardo; Ungaretti, Joaquín; Marchiano, Federico
Abstract: In recent years the percentage of Latin American immigrants in Argentina has grown all over the country. However, due to the economic crisis that the country is going through, the State offers economic support to the entire population, even to Latin American immigrants living in Argentina. Therefore, prejudiced attitudes towards these minority groups have increased. The aim of this study was to explore differences according to prejudice levels and country regions in the belief that Latin American immigrants who receive some kind of economic support do not really need it. Second, if the acceptance of granting economic support to immigrants can be explained by a theoretical model that includes conservative and self-enhancement values, right wing authoritarianism, social dominance orientation, and prejudice towards them. Participants were 1570 non-immigrants adults (between 18 and 75 years old, M age = 38.37; SD = 15.65), 55.1% female, grouped according to their region of residence (largest urban centers, smaller cities and border areas). Results of a path model indicate that values and ideological attitudes seem to underlie prejudice towards Latin American immigrants. Moreover, differences in the levels of prejudice according to the region where participants live, were found.